Permitted Laughter. Socialist, Post-Socialist and Never-Socialist Humour. - Szerszunowicz, Joanna (Folklore (14060957), 2010)
The article reviews the book "Permitted Laughter: Socialist, Post-Socialist and Never-Socialist Humour," edited by Arvo Krikmann and Liisi Laineste.